Learning to fail [ how society lets young people down - Abrams, Fran 1963- (Routledge, 2010)
Blending interviews with those most closely affected together with views from key commentators and experts the author creates a vivid picture of a system and societal failure, a failure both that is at once both embarrassing and avoidable